Evaluasi Emisi Kendaraan Bermotor Pada Jalan Tol Jakarta-Cikampek Menggunakan Mobile Versi 6.2. - A. Ikhsan Karim (Jurnal Teknik Sipil, 2010)
In general, vehicle emission in Jakarta â Cikampek toll road increases from the year 2003 to the year 2005, and its predicted to increase continuously. Regression analyses shown that vehicle volume have quadratic regression correlation with emission. Emission of HC, CO and NOx pollutant have calculated by MOBILE6.2 based on vehicle type and used fuel type including its pressure. It is also based on climate factors like air temperature in area wide, altitude, and relative humidity. Other factors that also determine are average speed and fraction of Vehicle Miles Traveled (VMT).Â The objective of this research are to calculate quantity of HC, CO, and NOx that produced by vehicle volume across Jakarta â Cikampek Toll Road, to generate relation pattern between traffic volume and emissions for every section in Jakarta - Cikampek Toll Road, and also predicted amount of emission will be happened in the year 2007.Â Analysis conducted at every section of Jakarta â Cikampek Toll Road section consist of 13 (thirteen) sections, including Cikampek direction and Jakarta direction. This is done because every section have different characteristic that is including vehicle volume factor, vehicle type, and used fuel type. These methods have better R2 value where its compared with method without division of direction and section.Â Hydro Carbon (HC) pollutant, at both Cikampek and Jakarta direction of year 2003 untill 2005 increases and it prediction increase continuously. HC pollutant increases with mean value 14.4 % at Cikampek direction and increasing 12.3 % at Jakarta direction with R2 mean value 0.964 at Cikampek direction and have R2 mean value 0.967 at Jakarta direction.For the pollutant of CO at both Cikampek and Jakarta direction of year 2003 untill 2005 increases and its predicted increase continuously, with mean increase 9.3% at Cikampek direction and have mean values 9.0 % increase at Jakarta direction. R2 of CO with vehicle number has mean value 0.911 at Cikampek direction and R2 mean 0.935 at Jakarta direction.Pollutant NOx also increases for both Cikampek direction and Jakarta direction of year 2003 until 2005 experiencing increase and it predict will be continuing increase. These pollutants have 6.6 % mean increase at Cikampek direction and 6.0 % at Jakarta direction. R2 mean value 0.865 at Cikampek direction and have R2 mean value 0.875 at Jakarta direction.The result of evaluation MOBILE6.2 emission factor against to Minister State of Environment Decree No.141/2003 for light duty gasoline vehicle type, obtained that the emission factor of carbon monoxide, hydrocarbon and nitrogen oxide pollutant, exceed determined threshold. The light duty diesel vehicles type, hydrocarbon and nitrogen oxides pollutant below emission threshold persistence. The medium-duty diesel vehicles and heavy-duty diesel vehicles type, hydrocarbon, carbon monoxide, and nitrogen oxide pollutant below emission threshold persistence.